Development of a photoinduced fragmentation ion trap for infrared multiple photon dissociation spectroscopy. (8th February 2020) - Penna, Tatiana C.; Cervi, Gustavo; Rodrigues‐Oliveira, André F.; Yamada, Bruno D.; Lima, Rafael Z.C.; Menegon, Jair J.; Bastos, Erick L.; Correra, Thiago C.
Abstract : Rationale: Methods for isomer discrimination by mass spectroscopy are of increasing interest. Here we describe the development of a three‐dimensional ion trap for infrared multiple photon dissociation (IRMPD) spectroscopy that enables the acquisition of the infrared spectrum of selected ions in the gas phase. This system is suitable for the study of a myriad of chemical systems, including isomer mixtures. Methods: A modified three‐dimensional ion trap was coupled to a CO2 laser and an optical parametric oscillator/optical parametric amplifier (OPO/OPA) system operating in the range 2300 to 4000 cm −1 . Density functional theory vibrational frequency calculations were carried out to support spectral assignments. Results: Detailed descriptions of the interface between the laser and the mass spectrometer, the hardware to control the laser systems, the automated system for IRMPD spectrum acquisition and data management are presented. The optimization of the crystal position of the OPO/OPA system to maximize the spectroscopic response under low‐power laser radiation is also discussed. Conclusions: OPO/OPA and CO2 laser‐assisted dissociation of gas‐phase ions was successfully achieved. The system was validated by acquiring the IRMPD spectra of model species and comparing with literature data. Two isomeric alkaloids of high economic importance were characterized to demonstrate the potential of this technique, which is now available as an open IRMPD spectroscopy facility in Brazil.